Mycelial Growth and Basidiocarp Production of Pleurotus Species in Substrates Supplemented with Fermented Plant Juice - Leilidyn Y. Zurbano; Diana A. Antones; Carla Mae C. Almoradie (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2022)
Pleurotus species are the common mushrooms popularly cultivated in the Philippines while Fermented Plant Juice (FPJ) is a known organic concoction which can help crops to grow. This study aimed to find out the effects of FPJ on the mycelial growth, basidiocarp production and sensory attributes of different species of Pleurotus in culture media, grain spawn and fruiting substrates supplemented with varying amounts of FPJ. The experiment was laid out in complete randomized design and replicated thrice for culture media and grain spawn; and replicated ten times for the fruiting substrates. P. florida in 20 ml culture media supplemented with 2.4 ml of the 120 ml FPJ solution had the fastest mycelial growth while P. citronipleatus in grain spawn supplemented with water had the fastest mycelial growth. P. ostreatus grown in 750 g dry weight of fruiting substrates supplemented with 150 ml of FPJ had 6.83 higher yield than the control, thus higher profitability and Return on Investment (ROI). Significant differences were also observed on the sensory attributes such as taste, aroma and general acceptability. Majority of the respondents liked P. florida which is considered as very much palatable. As the concentration of FPJ become higher, the taste becomes better.